The Alabama state constitution - Stewart, William H. (William Histaspas), 1939- (Oxford commentaries on the state constitutions of the United States., 2011)
The Alabama State Constitution provides an outstanding constitutional and historical account of the state's basic governing charter. In it, William H. Stewart, an authority on the state's political and constitutional history, provides an overview of important developments since 1819 along with an in-depth, section-by-section analysis of the entire constitution, detailing the many significant changes that have been made since its initial drafting. This treatment, along with a table of cases, index, and the bibliography provides an unsurpassed reference guide for students, scholars, and practiti.